Warehouse Layout Optimization and Material Handling Improvement for MSMEs: A Case Study of Toko Kharisma Batam - Ahmad, Farhan (Journal of Collaborative Industrial Management (JCIM), 2025)
This study focuses on improving warehouse management for Toko Kharisma, a Micro, Small, and Medium Enterprise (MSME) located in Batam City, which sells various school supplies. The initial assessment revealed inefficiencies in warehouse utilization, including disorganized storage, lack of material handling equipment, and manual processes that hinder operational efficiency. To address these issues, the proposed solutions include transitioning from folding storage to box storage, optimizing warehouse layout, implementing a systematic labeling system, and introducing material handling tools such as hand trolleys. Space requirements were calculated based on inventory volume and throughput to ensure effective design. The implementation plan also includes considerations for safety, accessibility, and workflow optimization. The expected outcomes of these improvements are enhanced inventory control, faster picking processes, reduced errors, and improved productivity. By adopting these strategies, Toko Kharisma can achieve better space utilization, operational efficiency, and sustainable business growth in a competitive retail environment.